Comparative study of reinforcement of Nano-SiO2 modified by poly(propylene glycol) phosphate ester versus oleic acid for waterborne polyurethane. (20th June 2018) - Gao, Xiaoyan; Mao, Yu; Ni, Lingli; Zhu, Xiufang; Zhou, Suqin; Yun, Shan; Hong, Kun; Wang, Jinquan
Abstract: In this work, in order to improve the dispersion and reinforcement of waterborne polyurethane (WPU), nano-SiO2 was modified with a amphiphilic polymeric surfactant poly(propylene glycol) phosphate (PPG Phosphate) and oleic acid for comparison, then incorporated into WPU through in situ polymerization. The results show that both of the PPG phosphate and oleic acid were successfully grafted onto nano-SiO2 surface and significantly improved its hydrophobic property. Scanning electron microscopy (SEM) observation reveals that PPG phosphate modified SiO2 nanoparticles had good compatibility with WPU and uniformly dispersed into WPU matrix. The results also show that the tensile strength, water resistance and thermal stability were all significantly improved by incorporation of nano-SiO2, especially PPG phosphate modified SiO2, which was attributed to its good dispersion in WPU and strong interface adhesion.